Language education in a multilingual city: The case of Limassol (UCL Press, 2016)
This paper aims to provide an overview of the current situation of multilingualism and language education in the city of Limassol, Cyprus. The multicultural character of Limassol is reflected in every aspect of city life, and is notably reflected in the sector of education. Therefore, there is a need to delve into the situation of language education, as this is manifested in affordances and policies, and in daily encounters, within the educational context. Drawing both from primary and secondary data, the study examines issues such as good practices in language learning for immigrants and the role of linguistic support.